Criminal analysis and its application in evaluating the performance of operational units of the Military Police of Alagoas (Research, Society and Development, 2024)
Criminal Analysis is a field of study designed to provide support for the management of public security in specific territories, which consists of a set of scientifically proven theories and techniques, capable of indicating critical points, systemic crises and possible solutions. In view of this, it directs police operations and optimizes existing resources, resulting in greater precision, reduced expenses, a greater sense of security and safe environments. In this context, the central objective of this study was to investigate how criminal analysis contributes to improving the operational practices of the Military Police, as well as improving public safety and reducing crime in the state of Alagoas. To this end, a systematic review of the literature was carried out, in which it was possible to collect bibliographic and documentary data on the topic. In parallel, information was sought on government websites, to acquire a more comprehensive view of the topic, incorporating practical and updated information available from reliable sources. Furthermore, it was noted that it is essential to structure a system of knowledge production in public security, capable of portraying the reality of the operational units of the PM/AL. In which, the careful selection of indicators must meet the expectations of decision makers, essential to guarantee the efficiency of the public security service offered by the Military Police of Alagoas.